Differences in expertise level for anticipatory skill between badminton `in game` strokes and serves - Robertson, K.; De Waelle, S.; Deconinck, F. J. A.; Lenoir, M. (International Journal of Sports Science & Coaching, 2022)
Over the past decades, researchers in racquet sports have been testing the role of visual anticipation and expert attunement to essential kinematic information for responding to `in game` strokes as well as serves. However, anticipatory behaviour to both strokes has not been compared directly, in spite of the different characteristics of these strokes in the context of badminton. Therefore, this study explored the differences in anticipatory behaviour among elite (n = 26), competitive (n = 15) and novices (n = 17) between in game strokes and serves in badminton by use of lab based video temporal occlusion tests. In two separate blocks, last strokes (LS) and serves (S) were presented with different occlusion points (- 200 and - 100 ms before shuttle-racquet contact, at shuttle-racquet contact, and + 100 after shuttle-racquet contact) in a randomised order. The main results from the analysis of variance were that (a) elites generally showed faster and more accurate responses, and (b) responses were generally faster in LS conditions than in serves. These results add to the current body of knowledge on anticipatory behaviour in racquet sports, and the practical implications for coaching and training are discussed.